2005
DOI: 10.1590/s0101-81752005000100025
|View full text |Cite
|
Sign up to set email alerts
|

Influência do substrato sobre o crescimento de Subulina octona (Brugüière) (Mollusca, Subulinidae), sob condições de laboratório

Abstract: Os moluscos pulmonados selecionam substratos adequados a sua sobrevivência, exibindo preferência por determinadas características químicas, físicas e estruturais. Esse fator ambiental afeta a reprodução e a sobrevivência desses animais. Todavia, ainda permanece obscuro que aspectos do ciclo de vida e comportamento são influenciados. O presente trabalho teve por objetivo determinar se o substrato influencia o crescimento de indivíduos da espécie Subulina octona (Brugüière, 1789), mantidos em areia, argila e ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The life history of these species is characterized by indeterminate growth, ovoviviparity and the release of calcified eggs (Dundee 1986; D’ávila and Bessa 2005a, b). Although L. unilamellata is also an ovoviviparous species with indeterminate growth, this species releases juveniles instead of eggs and present a more voluminous oviduct, compared to the other species.…”
Section: Discussionmentioning
confidence: 99%
“…The life history of these species is characterized by indeterminate growth, ovoviviparity and the release of calcified eggs (Dundee 1986; D’ávila and Bessa 2005a, b). Although L. unilamellata is also an ovoviviparous species with indeterminate growth, this species releases juveniles instead of eggs and present a more voluminous oviduct, compared to the other species.…”
Section: Discussionmentioning
confidence: 99%
“…For this species, there was a high correlation between body size and fecundity. Body weight, shell length and egg production are all correlated in land snails Subulina octona (Brugüière, 1789) (D'Ávila & Bessa 2005) and B. tenuissimus (Silva et al 2008), which suggests that H. semenlini gain reproductive success by breeding when they have reached a larger size.…”
Section: Discussionmentioning
confidence: 99%
“…Peake (1978) suggested that the nutritional content in individual eggs may be an important factor determining future growth patterns in pulmonates. Several works have also demonstrated that increased size is related to increased fecundity in many animals, including mollusks (Stearns & Koella 1986, Heller 2001, D'Ávila & Bessa 2005. Considering that isolated individuals were larger and produced more eggs per egg mass, further studies might investigate the relation between size and fecundity in O. matheroni.…”
Section: Discussionmentioning
confidence: 94%